Sacroiliac joint fusion guided by intraoperatively superimposed virtual surgical planning using simulated fluoroscopic images - Steven Lankheet; Nick Kampkuiper; Jorm Nellensteijn; Edsko Hekman; Gabriëlle Tuijthof; Femke Schröder; Maaike Koenrades (Brain and Spine)
Introduction: Sacroiliac joint fusion (SIJF) is a minimally invasive treatment for sacroiliac (SI) dysfunction. It involves placing implants through the SI joint under fluoroscopic guidance, requiring precise implant positioning to avoid nerve injury. Preoperative virtual surgical planning (VSP) aids in optimal positioning, but replicating it accurately in the operating room is challenging. Research question: This study aims to assess the feasibility of superimposing VSP onto intraoperative fluoroscopic images to aid in optimal implant placement. Material and methods: A method for intraoperative guidance using 3D/2D registration was developed and tested during SIJF as an available and potentially efficient alternative for costly and more invasive navigation systems. Preoperatively, a VSP is performed and simulated fluoroscopic images are generated from a preoperative CT scan. During surgery, the simulated image that visually best matches the intraoperative fluoroscopic image is selected. Subsequently, the VSP is superimposed onto the intraoperative fluoroscopic image using a developed script-based workflow. The surgeon then places the implants accordingly. Postoperative implant placement accuracy was evaluated. Results: Five interventions were performed on five patients, resulting in a total of 15 placed implants. Minor complications without clinical consequences occurred in one case, primarily attributable to the patient's anatomy and pathological manifestations. Mean deviations at implant apex and 3D angle were 4.7 ± 1.6 mm and 3.5 ± 1.3°, respectively. Discussion and conclusions: The developed intraoperative workflow was feasible and resulted in implants placed with low deviations from the VSP. Further research is needed to automate and validate this method in a larger cohort.